If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying abs(5x + -4) = -6 Reorder the terms: abs(-4 + 5x) = -6 (-4 * abs + 5x * abs) = -6 (-4abs + 5absx) = -6 Solving -4abs + 5absx = -6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: 6 + -4abs + 5absx = -6 + 6 Combine like terms: -6 + 6 = 0 6 + -4abs + 5absx = 0 The solution to this equation could not be determined.
| 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 | | 2(3x+1)-x=3 | | B-(2)=-11 | | 14-4y=y+x | | 1n+3-1=8 | | y-34=41/11(20-6) | | 3x-24=2x+26 | | y-34=41/11(18-6) | | 14x^2+9x=-1 | | -4+6(x-4)=15x+2-9x | | y-4/3-7=.25 | | 6n+3(n+2)=-(2n+7)+n | | -6m=42 | | 5x(2x+7)=2 | | 14x-8=34 | | 6-y/(-1)=0 | | 11-(3v+5)=3v-6 | | .15x=23 | | 3w+6-w=5w-2(w-3) | | 7y-4=216-2x | | 15-3.2x=-6.8 | | 8x+15=-57 | | (m+1.5)=1.5(2m+3) | | y=-x^2+8x-19 | | x+6(x-50)=750 | | 3y+2(y-5)=-1(3y-35)-y | | .55+q=.66 |